Supported liquid membrane extraction of reactive dye using fabricated polypropylene membrane - Harruddin, Norlisa (Soc Chemical Eng Japan, 2014)
This study investigates the transport of dye ions across a supported liquid membrane (SLM) by using tridodecylamine as a carrier and sodium hydroxide (NaOH) as a stripping agent. A microporous polypropylene membrane was used as a membrane support and prepared by the thermal induced phase separation (TIPS) technique. Two different TIPS techniques were used when preparing membranes: solidification and without solidification with polymer concentrations varied at 10, 15 and 20%. The results revealed that both techniques produced membranes with similar morphologies, but different pore size structures. The membrane with 15% polymer concentration which was prepared by the solidification technique produced a microporous membrane with a symmetric structure, defined pore size and high stability, and thus is feasible as the support material. The fabricated membrane was tested and the results revealed that 100% of reactive dyes was succesfully removed with 58% recovery from an aqueous solution. The fabricated membrane also exhibited high stability up to 25.5 h of extraction, thereby demonstrating an improved method for the separation of reactive dyes using a SLM.